2023
DOI: 10.1038/s41598-023-33150-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex and age affect acute and persisting COVID-19 illness

Abstract: Long COVID is associated with neurological and neuropsychiatric manifestations. We conducted an observational study on 97 patients with prior SARS-CoV-2 infection and persisting cognitive complaints that presented to the University Health Network Memory Clinic between October 2020 and December 2021. We assessed the main effects of sex, age, and their interaction on COVID-19 symptoms and outcomes. We also examined the relative contribution of demographics and acute COVID-19 presentation (assessed retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Lastly, the study had a higher representation of female participants. Numerous research studies [ 51 , 52 ] have indicated that females exhibit more symptoms than males, not only during the initial phase but also in the subsequent follow-up period. Males face an elevated likelihood of hospitalization and ICU admission, suggesting a greater potential for severe acute illness.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the study had a higher representation of female participants. Numerous research studies [ 51 , 52 ] have indicated that females exhibit more symptoms than males, not only during the initial phase but also in the subsequent follow-up period. Males face an elevated likelihood of hospitalization and ICU admission, suggesting a greater potential for severe acute illness.…”
Section: Discussionmentioning
confidence: 99%
“… 6 8 )—including the efficacy of the innate antiviral response—implying that poor viral control perpetuating ongoing inflammation, acute respiratory distress and end-organ damage may predispose individuals to ongoing symptomatology. Various predictors of PASC have been suggested, including female sex 7 , 9 12 , increased viral load at presentation 10 , lower peak SARS-CoV-2 antibody titers 6 , 7 , increased duration of hospital stay 13 and reactivation of latent Epstein–Barr virus infection 14 , 15 . Immune changes persisting for months following COVID-19 have also been detected 16 19 , although it is unclear whether these drive PASC or are independently reflective of acute disease severity.…”
Section: Mainmentioning
confidence: 99%
“…The aim of the present study was to investigate the alterations in metabolites of PAG pre-and post-COVID-19 infection in individuals who suffered from headaches during the acute phase of the disease, utilizing 1 H-MRS technology. Furthermore, due to the observed gender disparities in COVID-19 and the greater incidence of headaches in female patients (16)(17)(18)(19), the current study selectively enrolled female subjects to mitigate potential sex-related biases and improve the accuracy of the findings.…”
Section: Introductionmentioning
confidence: 99%